An Air‐Stable and Dendrite‐Free Li Anode for Highly Stable All‐Solid‐State Sulfide‐Based Li Batteries. Issue 38 (22nd August 2019) - Liang, Jianwen; Li, Xiaona; Zhao, Yang; Goncharova, Lyudmila V.; Li, Weihan; Adair, Keegan R.; Banis, Mohammad Norouzi; Hu, Yongfeng; Sham, Tsun‐Kong; Huang, Huan; Zhang, Li; Zhao, Shangqian; et al.
Abstract: Li metal is a promising anode material for all‐solid‐state batteries, owing to its high specific capacity and low electrochemical potential. However, direct contact of Li metal with most solid‐state electrolytes induces severe side reactions that can lead to dendrite formation and short circuits. Moreover, Li metal is unstable when exposed to air, leading to stringent processing requirements. Herein, it is reported that the Li3 PS4 /Li interface in all‐solid‐state batteries can be stabilized by an air‐stable Li x SiS y protection layer that is formed in situ on the surface of Li metal through a solution‐based method. Highly stable Li cycling for over 2000 h in symmetrical cells and a lifetime of over 100 cycles can be achieved for an all‐solid‐state LiCoO2 /Li3 PS4 /Li cell. Synchrotron‐based high energy X‐ray photoelectron spectroscopy in‐depth analysis demonstrates the distribution of different components within the protection layer. The in situ formation of an electronically insulating Li x SiS y protection layer with highly ionic conductivity provides an effective way to prevent Li dendrite formation in high‐energy all‐solid‐state Li metal batteries. Abstract : Air‐stable Li x SiS y protective layer is fabricated by a two‐step solution‐based reaction. The Li x SiS y layer can not only block the side reaction between Li and air but also allows excellent ion migration across the interface, and prevents interfacial reactions between Li and the sulfide electrolyte. Thus, stable cycling performance in sulfide‐electrolyte‐based all‐solid‐state lithium batteries is achieved.